Compendium on Jawahar Rozgar Yojana Design, Instruments and Instructions - Planning Commission (Planning Commission, 1991)
Merging the two erstwhile wage employment programmes. - National Rural Employment Programme (50:50 cost sharing basis between the Centre and the States) and Rural Landless Employment Guarantee Programme (fully funded by the Centre), the Jawahar Rozgar Yojana (JRY) was started w.e.f. April 1, 1989 (80:20 cost sharing basis between the Centre and the States). The Yojana has the twin objectives of generation of additional gainful employment for the unemployed and underemployed persons in rural areas and the creation of sustained employment by strengthening rural economic infrastructure as also assets in favour of rural poor for their direct and continuing benefits; and improvement in overall quality of life in the rural areas.
Programme Evaluation Organisation Planning Commission New Delhi